Practical rules : when we need them and when we don't - Goldman, Alan H., 1945- (Cambridge studies in philosophy., 2001)
The two dominant models in the current literature on rules are the particularist and normative accounts. Taking a position between these two extremes, Alan Goldman is the first to provide a systematic framework to clarify when we need to follow rules and when we ought not to do so.